Leopold Trénor Palavicino, a través de la Biografia d’un president de Lo Rat Penat (...), d’Amèlia Comba Comba (1965). - BANYULS, VÍCTOR PASTOR (Scripta, 2021)
This paper analyses the writer Leopold Trénor Palavicino based on information from the biography written by Amèlia Comba in 1965. the author’s pages provide a more in-depth perspective on the writer’s profile. Trénor, coming from a noble family, becomes a Catholic poet who can represent organizations like Lo Rat Penat, where he worked tirelessly to recover the Valencian language, literature and cultural heritage.